Beyond buying time: the role of plasticity in phenotypic adaptation to rapid environmental change - Fox, Rebecca J.; Donelson, Jennifer M.; Schunter, Celia; Ravasi, Timothy; Gaitán-Espitia, Juan D. (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2019)
How populations and species respond to modified environmental conditions is critical to their persistence both now and into the future, particularly given the increasing pace of environmental change. The process of adaptation to novel environmental conditions can occur via two mechanisms: (1) the expression of phenotypic plasticity (the ability of one genotype to express varying phenotypes when exposed to different environmental conditions), and (2) evolution via selection for particular phenotypes, resulting in the modification of genetic variation in the population. Plasticity, because it acts at the level of the individual, is often hailed as a rapid-response mechanism that will enable organisms to adapt and survive in our rapidly changing world. But plasticity can also retard adaptation by shifting the distribution of phenotypes in the population, shielding it from natural selection. In addition to which, not all plastic responses are adaptive—now well-documented in cases of ecological traps. In this theme issue, we aim to present a considered view of plasticity and the role it could play in facilitating or hindering adaption to environmental change. This introduction provides a re-examination of our current understanding of the role of phenotypic plasticity in adaptation and sets the theme issue's contributions in their broader context. Four key themes emerge: the need to measure plasticity across both space and time; the importance of the past in predicting the future; the importance of the link between plasticity and sexual selection; and the need to understand more about the nature of selection on plasticity itself. We conclude by advocating the need for cross-disciplinary collaborations to settle the question of whether plasticity will promote or retard species' rates of adaptation to ever-more stressful environmental conditions. This article is part of the theme issue ‘The role of plasticity in phenotypic adaptation to rapid environmental change’.